Republic of Uzbekistan : 2019 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2019)
This 2019 Article IV Consultation highlights that given its bulging working-age population, creating more and better jobs is the country's overarching priority. Uzbekistan has already implemented a first wave of important economic reforms, including foreign exchange liberalization, tax reform, and a major upgrade in statistics. Faced with a vast structural reform agenda, the authorities want to prioritize reforms that address the economy's most damaging distortions first. The main short-term macroeconomic stability challenge is to prevent a credit boom that could generate excessive external deficits and aggravate inflation pressures. A tight monetary stance and moderate fiscal deficits need to be maintained to support macroeconomic stability. Credit growth will need to slow significantly to assure the economy's external and internal balance. The sustainable development goals are anchoring the country's inclusive growth agenda, especially on education, health, public infrastructure, and financial inclusion. Moreover, the authorities are redesigning labor policies from scratch to help unskilled and other disadvantaged workers find more and better jobs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet